The nanny : a novel - Macmillan, Gilly (William Morrow, an imprint of HarperCollinsPublishers, 2019)
When her beloved nanny, Hannah, left without a trace in the summer of 1988, seven-year-old Jocelyn Holt was devastated. Haunted by the loss, Jo grew up bitter and distant, and eventually left her parents and Lake Hall, their faded aristocratic home, behind. Thirty years later, Jo returns to the house and is forced to confront her troubled relationship with her mother. But when human remains are accidentally uncovered in a lake on the estate, Jo begins to question everything she thought she knew. Then an unexpected visitor knocks on the door and Jo<U+2019>s world is destroyed again. Desperate to piece together the gaping holes in her memory, Jo must uncover who her nanny really was, why she left, and if she can trust her own mother<U+2026>